2012
DOI: 10.1088/0268-1242/27/3/035018
|View full text |Cite
|
Sign up to set email alerts
|

Tin oxide and indium oxide nanowire transport characteristics: influence of oxygen concentration during synthesis

Abstract: This study has analyzed the effects of varying oxygen flow rates on the formation of SnO 2 and In 2 O 3 nanowires using a vapor-liquid-solid technique and transistor characteristics. SnO 2 nanowires grow regardless of the change in the O 2 flow rate, whereas In 2 O 3 nanowire formation occurs only for an O 2 ratio below 0.2% in argon and transitions to nanoflakes or thin film at higher oxygen fractions. The oxygen fraction in the input gas stream also affects the transistor characteristics when these nanowires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…The Sb vacancy may derive from the surface defects, as reported in our previous work [25]. Additionally, other semiconductor-related studies described the vacancy-induced n-type conductivity in 1D nanoscale [26,27]. The inset revealed the SEM image of the single InSb nanowire connected to Cu electrodes.…”
Section: Resultssupporting
confidence: 52%
“…The Sb vacancy may derive from the surface defects, as reported in our previous work [25]. Additionally, other semiconductor-related studies described the vacancy-induced n-type conductivity in 1D nanoscale [26,27]. The inset revealed the SEM image of the single InSb nanowire connected to Cu electrodes.…”
Section: Resultssupporting
confidence: 52%
“…The extreme case of lack of oxygen during growth will not result in any ZnO NW growth whatsoever. Similar effects have been reported in In 2 O 3 system as well where nanowire formation, though random, occurs only for an oxygen ratio of less than 0.2% in argon and transitions to nanoflakes or thin films at higher oxygen fractions [28,29].…”
Section: Resultssupporting
confidence: 81%
“…The excess carrier may have originated from the Sb vacancies in InSb nanowires. A previous semiconductor-related work described the vacancy-induced high carrier concentration in 1-D nanoscale because the nanowires with a high surface-to-volume ratio easily led to more vacancies [23-26]. Moreover, previous works observed that the synthesized InSb nanowires indeed have a high electron concentration, which is about 3 orders of magnitude higher than those of bulk and thin films [13,14,19,27].…”
Section: Resultsmentioning
confidence: 99%